Oncolytic effect of Newcastle disease virus (NDV) strain AF2240 and V4-UPM on hypoxic and normoxic osteosarcoma cells - Nurneqman, Nashreq Kosni; Noraini, Abd-Aziz *; Abdul Rhaman, Omar; Saila, Ismail; Chia, Suet Lin (Malaysian Society of Microbiology, 2023)
Aims: Hypoxia is believed to be one of the key components contributing to the clinical resistance of cancer therapies. Alternative strategies are under investigation to overcome this resistance and the oncolytic virus stands amongst the others. Newcastle disease virus (NDV) has been demonstrated to possess oncolytic activity against cancer cells. The present study investigated the effects of oncolytic NDV strain AF2240 and V4-UPM on osteosarcoma cells (Saos-2) under normoxic and hypoxic conditions. Methodology and results: Results showed that the NDV strain AF2240 and V4-UPM could infect and kill normoxic and hypoxic Saos-2 cells equally well by inducing hypoxia-independent apoptosis, and S-phase cell cycle arrest under the microscopy examination, cell viability assay, Annexin V apoptosis assay and cell cycle analysis experiments. However, the Velogenic NDV strain AF2240 excelled over the lentogenic NDV V4-UPM with increased oncolytic effects in Saos-2 cells. Conclusion, significance and impact of study: In a nutshell, normoxia or hypoxia microenvironment has little effect on NDV-induced oncolysis of Saos-2 cancer cells which poses as a potential agent for the treatment of resistant cancer.